2019
DOI: 10.1021/acschembio.9b00373
|View full text |Cite
|
Sign up to set email alerts
|

Hijacking the Heme Acquisition System of Pseudomonas aeruginosa for the Delivery of Phthalocyanine as an Antimicrobial

Abstract: To survive in the iron-devoid environment of their host, pathogenic bacteria have devised multifarious cunning tactics such as evolving intricate heme transport systems to pirate extracellular heme. Yet, the potential of heme transport systems as antimicrobial targets has not been explored. Herein we developed a strategy to deliver antimicrobials by exploiting the extracellular heme acquisition system protein A (HasA) of Pseudomonas aeruginosa. We demonstrated that, analogous to heme uptake, HasA can specifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 29 publications
(47 reference statements)
1
37
0
1
Order By: Relevance
“…Instead, the removal of central conjugated Zn 2+ rather drastically enhanced its dark antagonist activity [51]. Interestingly, in a separate report, it was found that a completely water-insoluble gallium-conjugated phthalocyanine without any peripheral substitutions (GaPc) could be bound and dissolved by the bacterial heme acquisition system (Has) protein A (HasA) transported via HasA receptors into Pseudomonas aeruginosa bacterial cells for subsequent photodynamic inactivation [52]. The recognition of SALPC by CCK2R, Zn-DIGP by CXCR3, and Ga-Pc by HasA all clearly indicate that phthalocyanines per se in the complete absence of light irradiation are an important class of bioeffective molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the removal of central conjugated Zn 2+ rather drastically enhanced its dark antagonist activity [51]. Interestingly, in a separate report, it was found that a completely water-insoluble gallium-conjugated phthalocyanine without any peripheral substitutions (GaPc) could be bound and dissolved by the bacterial heme acquisition system (Has) protein A (HasA) transported via HasA receptors into Pseudomonas aeruginosa bacterial cells for subsequent photodynamic inactivation [52]. The recognition of SALPC by CCK2R, Zn-DIGP by CXCR3, and Ga-Pc by HasA all clearly indicate that phthalocyanines per se in the complete absence of light irradiation are an important class of bioeffective molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Recently an interesting strategy was developed by Shisaka et al,w hereby the extracellular heme acquisition system protein A( HasA) wasu sed to accumulate water-insoluble GaPc into the intracellulars pace of P. aeruginosa via the protein recognition of HasA by the outer membrane receptor HasR (Figure 7b). [69] An irradiationt ime of only 10 min at al ight irradianceo f 10 mW cm À2 was sufficient to sterilizeo ver 99.99 %o fb acteria when 42 was used as PS. This strategy shows that water-soluble protein carriers may be able to successfully deliver PS to target bacteria.…”
Section: Phthalocyanines Containing Other Metal Centresmentioning
confidence: 97%
“…by the outer membrane receptor HasR (Figure 7 b). [69] An irradiation time of only 10 min at a light irradiance of 10 mW cm −2 was sufficient to sterilize over 99.99 % of bacteria when 42 was used as PS. This strategy shows that water‐soluble protein carriers may be able to successfully deliver PS to target bacteria.…”
Section: Molecular Photosensitizersmentioning
confidence: 98%
“…1a), can accept various bulky synthetic metalloporphyrins, such as diphenylporphyrin. [34][35][36][37] Yet, at this time, we were unable to incorporate bulkier TPP into HasA and concluded that this may not be possible, 34,35 and that the TPP skeleton may be incompatible for incorporation into unadulterated proteins and application with natural biological systems.…”
mentioning
confidence: 87%